Application of micro expansion cement in Pavement Base - Hongjun Li (E3S Web of Conferences, 2020)
Cement stabilized macadam base is widely used as a road building material in various grades of highways. Based on the law that the base cracking is mainly affected by the shrinkage of cement stabilization materials, this paper introduces the method of adding micro-expanding cement to the base that can effectively reduce the hydration shrinkage coefficient and dryness shrink factor. At the same time, it is pointed out that strict control of the amount of micro-expansion cement and the quality of the construction can also effectively reduce the occurrence of cracks in the base.